2020
DOI: 10.1002/pssa.201900984
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and Piezoelectric Properties of BiFeO3‐Based Piezoelectric Ceramics

Abstract: Bismuth ferrite‐based bulk ceramics (1–x)Bi0.97Sm0.08FeO3–xBaTiO3 (BSF–xBT with x = 0.00 FC, x = 0.00 WQ, x = 0.01 WQ, x = 0.03 WQ, and x = 0.05 WQ, where FC is the furnace cooled and WQ is the water quenched) are synthesized by a conventional solid‐state reaction method followed by WQ process. The WQ procedure (compared with FC) dramatically improves the remnant polarization (Pr) of x = 0.00 ceramic from 11 to 21 μC cm−2. BT incorporation gradually reduces the coercive field (Ec) and Pr significantly enhances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…On the other hand, the obtained loops also suggested the ferroelectric nature of BFO and GFO, which supports previous literatures. [20,21]…”
Section: Characterizations Of Filler Materialsmentioning
confidence: 99%
“…On the other hand, the obtained loops also suggested the ferroelectric nature of BFO and GFO, which supports previous literatures. [20,21]…”
Section: Characterizations Of Filler Materialsmentioning
confidence: 99%
“…Besides that, the phase formation and thermodynamics of BiFeO 3 crystals from the Bi 2 O 3 -Fe 2 O 3 pseudo-binary system have been extensively studied. [19][20][21][22][23] Meanwhile, the research on the morphological evolution of iron-sillenite Bi 25 FeO 40 single crystal from the Bi 2 O 3 -Fe 2 O 3 melt is still scarce. Therefore, investigating the growth mechanism to achieve high-quality single crystals is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, considerable efforts have been made by many researchers to develop lead-free high-temperature piezoelectric materials, especially those with relatively inexpensive raw materials, such as BiFeO 3 -BaTiO 3 (BF-BT)-based ceramics. [10][11][12][13][14] Regrettably, the practical use of BF-BT-based ceramics is hindered by low DC resistivity as well as poor piezoelectricity, although they possess an extremely high Curie temperature (T C ¼ 619 C). [15] It is found that both MnO 2 doping and Bi excess can raise the resistance of BF-BT, thereby making it polarizable.…”
Section: Introductionmentioning
confidence: 99%